2004
DOI: 10.1002/masy.200450906
|View full text |Cite
|
Sign up to set email alerts
|

D/A‐metallocenes: the new dimension in catalyst design

Abstract: D/A metallocenes constitute a novel unique class of catalysts, in that they are able to express structural information within the elementary steps of the catalytic cycle out of bridged as well as out of unbridged states due to the coexistence of donor (D) and acceptor (A) atoms in complex sandwich structures. Highly polarized transannular bridging interactions as well as Lewis basic and Lewis acidic functionalities in unbridged states are the prerequisites which define a modular highly flexible catalyst system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Other nontraditional bridges include R 2 E (E = Ge, Sn) (35), as well as an alkyl boryl (36), and one with nitrogen that can bind directly to the transition metal (37). The bridge shown in 6 employs a Lewis acid-Lewis base interaction between P and B atoms; the metallocene gives highly isotactic polypropylene (iPP) at low temperatures, indicating the bridge can be robust under polymerization conditions (38,39 (44), which is proposed (45) to have a half-sandwich chromium center as shown in equation 7. This catalyst exhibits facile chain transfer to H 2 , poor comonomer incorporation, and polymers of fairly broad MWD.…”
Section: Bridged Sandwich Complexes Bridged (Or Ansa-) Metallocenesmentioning
confidence: 97%
“…Other nontraditional bridges include R 2 E (E = Ge, Sn) (35), as well as an alkyl boryl (36), and one with nitrogen that can bind directly to the transition metal (37). The bridge shown in 6 employs a Lewis acid-Lewis base interaction between P and B atoms; the metallocene gives highly isotactic polypropylene (iPP) at low temperatures, indicating the bridge can be robust under polymerization conditions (38,39 (44), which is proposed (45) to have a half-sandwich chromium center as shown in equation 7. This catalyst exhibits facile chain transfer to H 2 , poor comonomer incorporation, and polymers of fairly broad MWD.…”
Section: Bridged Sandwich Complexes Bridged (Or Ansa-) Metallocenesmentioning
confidence: 97%
“…The ansa catalysts show higher comonomer incorporation than non‐bridged catalysts 10, 27–30. Since the discovery of bridged catalysts, much research has been focused on catalyst design and the role of the bridges in catalytic performance 30–36. In recent research it has been found that addition of substituents to ligands can improve catalyst activity and comonomer incorporation ability 3, 37–43.…”
Section: Introductionmentioning
confidence: 99%
“…During the past 25 years, metallocene complexes have been extensively studied as catalysts for the homogeneous and heterogeneous polymerization of α‐olefins 1–26. For industrial applications, heterogeneous catalyst systems are preferred since the amount of the expensive cocatalyst MAO27–35 can be significantly reduced and “reactor fouling” is avoided.…”
Section: Introductionmentioning
confidence: 99%